FNEW DATA ON TYPE-LOCALITY SOROSITE: COMPOSITIONAL VARIATIONS, ZONING, AND A REVISED FORMULA - Barkov A.Y.; Martin R.F.; Shi L. (My University, 2006)
We report new results of multiple EMP analyses of sorosite from the Baimka Au-PGE placer deposit, western Chukotka, northeastern Russia. It occurs as (1) relatively large (0.24).4 mm) euhedral, cryptically zoned hexagonal grains, with Fe-Ni-rich zones in the core, (2) large irregular or skeletal grains, and (3) elongate subhedral to euhedral (hexagonal), or anhedral micrograins (≤20 μm). They all are hosted by native tin (Sb-bearing), and are associated with stistaite Sn1+xSb and herzenbergite SnS. The Fe content of these zoned grains decreases from the center (3 wt.%) toward the edge (≤0.05 wt.%). The Ni content also decreases from the core (1.2 wt.%) to the periphery (<0.02 wt.%). The level of Sb covaries positively with Fe and Ni; it is enriched in the core (5.8%) relative to the periphery (4%). The incorporation of Fe+Ni is thus somehow controlled by Sb. Values of 100 Fe / (Fe + Ni) also exhibit cryptic variations. On the basis of our results (214 EMP analyses acquired with three different instruments and sets of standards), the average composition of sorosite, recalculated for (Sn + Sb) = 1 apfu, is: (Cu1.09-1.14 Fe0.02-0.05 Ni0.01-0.02) ∑1.15-1.17 (Sn0.91-0.93 Sb0.07-0.09) ∑1.00; the observed ranges are: Cu 0.97-1.19, Fe 0-0.13, Ni 0-0.04, Co <0.01, ∑Me 1.10-1.21, Sn 0.90-0.99, and Sb ≤0.01-0.10 apfu. The revised formula for sorosite is (Cu,Fe)1+x(Sn,Sb), where 0.1 ≤ × ≤ 0.2. The excess Cu atoms (i.e., 0.1-0.2 Me apfu), relative to CuSn, presumably occupy the trigonal-bipyramidal holes associated with interstitial sites of the NiAs-type lattice. The incorporation of Sb in sorosite is governed by two mechanisms of substitution: [Cu + Sn = (Fe+Ni) + Sb], consistent with the observed solid-solution of Cu1+xSn (sorosite) with related NiAs-type antimonides: Fe1+xSb (unnamed) and Ni1+xSb (breithauptite), and by the Sb-for-Sn mechanism, which operates in Fe-Ni-poor sorosite. Sorosite likely crystallized from a late-stage or residual Sn-Sb-Cu-Fe-Ni-bearing liquid, under conditions of low f(O2) and f(S2); the inferred sequence of crystallization is: (1) large euhedral grains (Fe-Ni-Sb-rich core → Fe-Ni-Sb-poor periphery) → (2) large irregular grains (Fe-Ni-poor) → (3) various micrograins (Ni-Fe-poor, poorer in Sb than the large grains). Crystallization occurred over the range >415°-227°C, the latter being the eutectic temperature in the binary system Cu-Sn. A mineralized mafic rock (gabbro, gabbro-diorite, or clinopyroxenite) associated with the Yegdegkychsky gabbro - diorite - syenite - monzonite complex in the placer area could be a potential primary source for the sorosite-bearing mineralization.
Keywords: (CU,FE)1+X(SN,SB); BAIMKA; CHUKOTKA; CRYPTIC ZONING; CU-SN SYSTEM; GOLD-PGE PLACER DEPOSIT; INTERMETALLIC COMPOUND; MECHANISMS OF SUBSTITUTION; NICKELINE-TYPE STANNIDE; RUSSIA; SN-SB-CU MINERALIZATION; SOLID-SOLUTION SERIES; SOROSITE